Effect of distillery wastewater on chemical composition and microbial community of Sorghum propinquum silage during micro-permeation of air - Huang, Xiaokang; Lu, Guangrou; Li, Lin; Liao, Chaosheng; Tang, Xiaolong; Chen, Cheng; Zhang, Mingjie; Li, Ping; Chen, Chao (Frontiers in Industrial Microbiology, 2024)
The aim of this study was to investigate the effect of distillery wastewater (DWW) on the nutrient composition, fermentation quality and microbial community of Sorghum propinquum silage during the micro-permeation of air. S. propinquum without (CK) or with L. buchneri, (LAB), distillery wastewater yellow serofluid (Y) and distillery spent wash (S) was ensiled for 60 days, and then subjected to a micro-permeation stability of air test for 6 days. After 60 days of storage, treatments with DWW and LAB decreased the loss of DM, inhibited the degradation of protein and reduced the production of ammonia nitrogen in silage relative to the control. In particular, S. propinquum silage treated with yellow serofluid sustained higher levels. Moreover, the addition of DWW resulted in higher levels of acetic and propionic acid than the other treatments. During the micro-permeation of air, the addition of DWW was effective in inhibiting the reduction of lactic acid content, and unique genera Roseburia and Faecalibacterium, which are beneficial for livestock production, discovered in DWW-treated S. propinquum silage. In conclusion, the addition of DWW was efficacious in improving the nutritional composition and microbial community of S. propinquum silage during the micro-permeation of air.